Justification of technological parameters of the cream production with sapropel extract - Oksana Strus; Nataliia Polovko; Oksana Yezerska (Pensoft Publishers, 2019)
The aim of the research was to substantiate the technological parameters of cream production with the sapropel extract and work out the technological scheme for its production. In this study, extract of sapropel from the Prybych deposit, emulsion base, containing corn oil, emulsifier No.1, cetylstearyl alcohol, nisin, euxyl K 100 and purified water were employed. To carry out the research, a set of methods to analyse colloidal and thermal stability was used. Rheological properties of the samples were determined. The method of microscopic analysis was carried out to analyse the stability of the emulsion system. It was proved experimentally that, when producing the cream, it is appropriate to use the phase inversion method, and the emulsification needs to be carried out at 5000 r/m for 20 min. Size and shape of the sample drops, obtained at 5000 r/m, were monodisperse and more uniform, most of which range from 2 to 3 microns that indicates the system stability. The following parameters of technological process were determined: mixing temperature conditions, speed of homogenisation and mixing time.